Style, rhetoric, and rhythm essays. - Croll, Morris W. (Morris William), 1872-1947 (Princeton legacy library., 1966)
A closely documented, balanced account of the bitter political struggle in May and June of 1960 when thousands of Japanese rioted in protest against the revised treaty. William W. Lockwood calls it "one of the best case studies of Japanese political behavior ever written."Originally published in 1966. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905